The Experiences of Learners with Disabilities in Mainstream Vocational Training in Nepal - Eka Raj Adhikari (European Research Network Vocational Education and Training (VETNET), 2018)
Context: This article explores the lived experiences of learners with disabilities who were attending short-term skills-based training programs in Nepal. The research questions addressed were how the learners with disabilities had been experiencing learning with their peers without disabilities and whether the vocational training was inclusive from the perspectives of learners with disabilities. Approach: Based on a phenomenological design, eight learners with disabilities were purposively selected. In-depth interviews were held with the participants. Data were collected in the forms of audiotaped recordings, field notes, and institutional records. The thematic analysis technique was employed to explicate the transcribed data. Results: The results showed that learners with disabilities faced difficulty in commuting to and from the training center. The physical learning environment was insufficiently accessible, and this affected the learning of students with disabilities. Although the learners with physical disabilities had no problem in understanding the subject matter taught in the mainstream classrooms, the learners with visual impairments and those who were with hard of hearing had, at times, difficulty in following their instructors. The learners with disabilities had trouble with socialization and with forming friendships though they had supportive instructors. The participants' statements revealed that the existing inclusion practices were not enough to address the needs of persons with disabilities. However, they viewed inclusion as a much better option to cater to the needs of differently abled people. Conclusion: Inclusive technical and vocational education and training (TVET) is in practice throughout the world. This qualitative research paper has presented the perspectives of learners with disabilities (LWDs) about the inclusive practices in the Nepalese TVET sector. More importantly, this study has given a voice to the LWDs from mainstream vocational training centers in Nepal.